(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to fit the number of exercises proposed and the capabilities of the research sample, and learn about the impact on some of the kinetic capabilities and counter-attacks of the players epee. The researcher used the experimental method is the same group. And it included a sample search (8) players representing the central Iraqi National Youth team in the fencing weapon Blinds, were selected purposively, and mayors of the researcher to the number of tests the attack counter in fencing suit with a sample search, and then deliberately researcher to develop training curriculum using the proposed and stomach exercises by the researcher who carried out took ten weeks and by (30) and a training unit The researcher found that the proposed exercises a remarkable influence on the players’ performance by comparing pretest and posttest sample search results. As the researcher recommends the need to take the results of this study and dissemination and the emphasis on the training of fencing halls equipped with modern means of training, of its own positive impact in the improvement and development. It should be of interest to provide the use of modern technology in the functional capacity tests in the schools athletic talent fencing and conduct studies on the effect of exercise on the proposed according to the bio-energy systems in other functional mobility and skill with a weapon capabilities epee fencing.